2018
DOI: 10.1089/scd.2017.0225
|View full text |Cite
|
Sign up to set email alerts
|

Interferon-γ Promotes Neuronal Repair by Transplanted Neural Stem Cells in Ischemic Rats

Abstract: Ischemic stroke represents the leading cause of adult neurological disability, with no effective therapeutic strategy. Stem cell transplantation promises a new promising for treating stroke, through cell replacement and cytokine paracrine. However, due to the effect of hostile immune microenvironment, the survival and differentiation of stem cells are limited in vivo. Furthermore, the delayed inflammatory response to stroke induced secondary neurological injury. IFN-γ as pro-inflammatory cytokine has the poten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 39 publications
0
16
0
Order By: Relevance
“…Co-injection of neural stem cells and IFN-γ have been shown to improve therapeutic outcomes in a model of ischaemic stroke in rats. IFN-γ treatment significantly increased neurogenesis in vivo, and induced levels of subsequent neuronal differentiation of cytokines BDNF, VEGF, IGF-1 and TGF-β (34).…”
Section: Discussionmentioning
confidence: 96%
“…Co-injection of neural stem cells and IFN-γ have been shown to improve therapeutic outcomes in a model of ischaemic stroke in rats. IFN-γ treatment significantly increased neurogenesis in vivo, and induced levels of subsequent neuronal differentiation of cytokines BDNF, VEGF, IGF-1 and TGF-β (34).…”
Section: Discussionmentioning
confidence: 96%
“…However, IFN-γ does not hamper the ability of NSCs in vitro . Study[88] have shown that co-delivery of IFN-γ (50 ng) enhanced the effects of transplanted NSCs in ischemic rats. The study found that in the combination-treatment group, neurogenesis was significantly increased when compared to other groups in vivo .…”
Section: Optimizing the Therapeutic Efficacy Of Neural Stem Cell Tranmentioning
confidence: 99%
“…Moreover, co-treatment with IFN-γ and NSCs provided additional beneficial neurological outcomes. Thus, low concentrations of IFN-γ can mediate NSC functions and facilitate their ability for neurological repair[88].…”
Section: Optimizing the Therapeutic Efficacy Of Neural Stem Cell Tranmentioning
confidence: 99%
“…Previous researches have shown that cell proliferation can be found in subventricular zone in rat model disposed by the middle cerebral artery occlusion (MCAO), suggesting that endogenous recovery process is started after stroke [54][55][56][57]. However, endogenous resilience may be limited due to hostile immune microenvironment over time [56,58]. In addition, the delayed inflammatory response to stroke leads to secondary neurological injury [52,58].…”
Section: Exosomes Transplantation Therapy Directlymentioning
confidence: 99%
“…However, endogenous resilience may be limited due to hostile immune microenvironment over time [56,58]. In addition, the delayed inflammatory response to stroke leads to secondary neurological injury [52,58]. Insufficient endogenous stem cells after stroke can result in weak regeneration of nerve cells in the damaged area and slowdown in tissue function recovery.…”
Section: Exosomes Transplantation Therapy Directlymentioning
confidence: 99%